Load-shedding and the Declining Energy Availability Factor: A Case Study of a South African Power Station - Kock, Z.; Govender, Krishna K. (Mediterranean Journal of Social Sciences, 2021)
Through a mixed methods study, which included a survey among a stratified sample of 70 employees and interviews with 11 managers, this paper reports on the factors which led to a decline in power generation by Eskom’s Camden Power Station. The impact of the declining energy available factor (EAF) was significant, primarily on economic activities, employment, revenue loss due to load-shedding, and corporate social responsibility. The main causes of the declining EAF included leadership instability, financial constraints, inadequate plant maintenance, process-related challenges, bottle necks in the procurement of replacement parts, poor quality spare parts, high staff turnover, poor employee morale, poor workmanship and poor quality coal.It is recommended that funding for EAF related projects be prioritized, the performance of the acting managers needs to closely managed, sources of coal be streamlined, the training of quality control personnel and contract supervisors be improved and staff morale be urgently addressed. Received: 7 September 2021 / Accepted: 7 October 2021 / Published: 5 November 2021